2021
DOI: 10.2196/26254
|View full text |Cite
|
Sign up to set email alerts
|

Using Twitter to Understand the COVID-19 Experiences of People With Dementia: Infodemiology Study

Abstract: Background The COVID-19 pandemic is affecting people with dementia in numerous ways. Nevertheless, there is a paucity of research on the COVID-19 impact on people with dementia and their care partners. Objective Using Twitter, the purpose of this study is to understand the experiences of COVID-19 for people with dementia and their care partners. Methods We collected tweets on COVID-19 and dementia using the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 12 publications
2
36
1
Order By: Relevance
“…Therefore, conclusions drawn from this review should be interpreted with caution and follow-up systematic reviews with higher quality data are warranted. It is worth noting that evidence provided in this review are in accordance with more recent findings being published on an ongoing basis (e.g., [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]). Despite these limitations, the current systematic review allowed to highlight the extent of the effects of the pandemic, and the results established should be taken into consideration by healthcare practitioners, institutions, and policymakers to ensure that proper measures are employed to protect this population from additional harm.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, conclusions drawn from this review should be interpreted with caution and follow-up systematic reviews with higher quality data are warranted. It is worth noting that evidence provided in this review are in accordance with more recent findings being published on an ongoing basis (e.g., [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]). Despite these limitations, the current systematic review allowed to highlight the extent of the effects of the pandemic, and the results established should be taken into consideration by healthcare practitioners, institutions, and policymakers to ensure that proper measures are employed to protect this population from additional harm.…”
Section: Discussionsupporting
confidence: 90%
“…Many improvement initiatives focused on non-pharmacological measures including cognitive stimulation, nutritional optimisations, increased walking, and trying to maintain social interaction [67]. Studies suggested that poor mental health outcomes associated with lockdown can be mitigated with thoughtful intervention and ongoing evaluation with clinical information systems [71][72][73]. The European Geriatric Medicine Society advocated for the use of a programme known as MATCH (maintenance of autonomy through exercise care during hospitalisation) involving the use of a decision tree to cater to the various fitness levels of residents [50].…”
Section: Physical and Mental Health Support For Residentsmentioning
confidence: 99%
“…This study employed content analysis of social media data in relation to COVID-19 testing [23][24][25], complemented by contextual epidemic data. COVID-19 epidemic data from the United Kingdom and mainland China were derived for trend analysis [26,27].…”
Section: Discussionmentioning
confidence: 99%